Hematopoietic Cell Kinase (HCK) Is Essential for NLRP3 Inflammasome Activation and Lipopolysaccharide-Induced Inflammatory Response In Vivo - Kong, Xiangxi; Liao, Yajin; Zhou, Lujun; Zhang, Ying; Cheng, Jinbo; Yuan, Zengqiang; Wang, Shukun (Frontiers in Pharmacology, 2020)
Activation of the NLRP3 inflammasome results in caspase 1 cleavage, which subsequently leads to IL-1β and IL-18 secretion, as well as pyroptosis, and aberrant activation of the inflammasome is involved in several diseases such as type 2 diabetes, atherosclerosis, multiple sclerosis, Parkinson’s disease, and Alzheimer’s disease. NLRP3 activity is regulated by various kinases. Genetic and pharmacological inhibition of the hematopoietic cell kinase (HCK), a member of the Src family of non-receptor tyrosine kinases (NRTKs) primarily expressed in myeloid cells, has previously been shown to ameliorate inflammation, indicating that it may be involved in regulation of microglia function. However, the underlying mechanism is not known. Hence, in this study, we aimed to investigate the role of HCK in NLRP3 inflammasome activation. We demonstrated that HCK silencing inhibited NLRP3 inflammasome activation. Furthermore, the HCK-specific inhibitor, A419259, attenuated the release of IL-1β and caspase 1(P20) from macrophages and microglia and reduced the formation of the apoptosis-associated speck-like protein with a CARD domain (ASC) oligomer. We also observed that HCK binds to full length NLRP3 and its NBD(NACHT) and LRR domains, but not to the PYD domain. In vivo, the HCK inhibitor attenuated the LPS-induced inflammatory response in the liver of LPS-challenged mice. Collectively, these results suggested that HCK plays a critical role in NLRP3 inflammasome activation. Our results will enhance current understanding regarding the effectiveness of HCK inhibitors for treating acute inflammatory diseases.